O controle judicial de políticas públicas e sua legitimidade democrática - Amorim, Maurício Oliveira (2015)
This study aims to analyze the judicial control of public policies. Thus, the doctrinal concept of these policies will be explained as well as the delimitation of the political harvest in which they develop. A brief overview of the division of powers is required, in order to better define what can be considered as judicial activism. On this same theme of activism, it will be shown that there is no consensus on their classification, but it depends on the time and place to be analyzed. A relevant discussion on the possible Reserve theory is demonstrated, as well as whether or not their use when analyzing the legitimacy of judicial intervention in the sphere of activities of the other branches of government. Finally, the subject of judicial intervention at the present time, and its possible consequences for democracy will be studied.